Satellite DNA of lizards of the genus Lacerta s. str. (the group L. agilis), the family Lacertidae - Grechko, V. V.; Ciobanu, D. G.; Darevsky, I. S.; Kramerov, D. A. (Doklady. Biochemistry and biophysics, 2005)
(ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT]